Perbedaan Pengaruh Multiple Micro Nutrient (MMN) Dan Moringa Oleifera Terhadap Kadar Hemoglobin Tikus Bunting - Dwi Retna Prihati; RD Rahayu (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Multiple Micro Nutrient (MMN), Moringa Oleifera, Hemoglobin. Pregnant women are one of the vulnerable groups that may have anemia because hemodelusi events that occur during pregnancy. Multiple Micro Nutrient (MMN) is a supplement that contains multivitamins, iron and folate were given to pregnant women as one of the programs of the Ministry of Health of Indonesia in its efforts to prevent anemia during pregnancy. A survey found that 70% of pregnant women do not like the taste of Multiple Micro Nutrient (MMN) and in addition also the mother complain nausea, dizziness, palpitations, shortness of breath so hot and these supplements are not consumed and not consumed until exhausted if 120 tablets, See the above phenomenon it is necessary to alternative solutions, such as by utilizing vegetables such as Moringa oleifera. Iron content in 100 gr dry leave Moringa oleifera is 28,2 mg. The purpose of this study was to prove that no difference between the influence of Multiple Micro Nutrient (MMN) and Moringa oleifera against hemoglobin levels of pregnant rats. Experiment laboratory study design was a randomized design with a pre-post test with a control group. The population is the first day of the pregnant rats, large samples of 24 rats. Twenty-four pregnant rats were randomly divided into 3 groups. Statistical analysis using Independent T-test. Significant value in this study was p <0.05. The results Independent T-test showed that Moringa oleifera has the same effect with Multiple Micro Nutrient in preventing a decline in hemoglobin levels in pregnant rats (P = 0,537).